Allograft tolerance after adult living donor liver transplantation: a case-control study - Mohamed S. Habl; Moataz Maher Emara; Reham A. Zayed; Ahmed M. Sultan; Ahmed Elsabagh; Ahmed Marwan Elsaid; Ehab E. Abdel-khalek; Mohamed M. El-Saadany; Mohamed Abdel Wahab; Ahmed Shehta (BMC Surgery)
Abstract Background To investigate the incidence and potential predictors of immune tolerance among adult living donor liver transplant (LDLT) recipients. Methods This case-control study included adult recipients who underwent LDLT between May 2004 and January 2018, with at least a 5-year follow-up after LDLT. We divided the study recipients into two groups: Group 1 (Tolerance Group) included recipients who achieved operational or prope tolerance for at least one year; Group 2 (Control Group) included recipients who did not achieve tolerance. We used logistic regression analysis to study the potential predictors of tolerance after LDLT. Results We included 368 recipients, 275 (74.7%) in Group 1 and 93 (25.3%) in Group 2. Operational tolerance occurred in 13/275 (4.7%) recipients and prope tolerance in 262/275 (95.3%) recipients. Age was significantly higher in Group 1. The median time for tolerance among the study recipients was 60 months (36–168). During follow-up, Group 1 showed lower serum levels of bilirubin, liver enzymes, alkaline phosphatase, and gamma-glutamyl transferase. Group 1 had a lower incidence of acute cellular rejection (ACR), recurrent viral hepatitis, and biliary complications. Logistic regression identified preoperative MELD, indication for LDLT, ACR, recurrent viral hepatitis, and biliary complications as significant predictors for allograft tolerance after LDLT. Conclusion Allograft tolerance occurred in 74.7% of this cohort. We suggest that the MELD score, indication for LT, ACR, recurrent viral hepatitis, and biliary complications are predictors of allograft tolerance after LDLT.